Political dimenson of land reforms in India - "Eashvaraiah, P." (New Delhi, 1985)
The book is politico-historical study of the policy logic of peaceful and piecemeal and reforms in India with special reference to A.P. (Telan gana Area) Tenancy and Agricul tural Lands Act 1950. The land problem in the erstwhile Hyderabad State, the failure of the various mea sures taken by the Nizam Government and how the peasants waged an armed struggle against the existing feudal system and started implementing revolutionary land reforms form the background of the study. The way this process was obstructed by the Government of India, the process of enactment of legal and peaceful measures of land reforms to pacify the peasantry by the Congress Government of Hyderabad and the various problems involved in the process from the main content of the study.
Keywords: Land reform in India